2006
DOI: 10.1002/jbm.a.30863
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of uniform radiopaque polystyrene microspheres for X‐ray imaging by a single‐step swelling process

Abstract: Uniform radiopaque polystyrene microspheres of approximately 2.3 +/- 0.2 microm were prepared by a single-step swelling of 2.3 +/- 0.2 microm polystyrene template microspheres, dispersed in an aqueous solution with methylene chloride emulsion droplets containing 2,3,5-triiodobenzoylethyl ester. After completing the swelling process, the methylene chloride was evaporated in order to lock the 2,3,5-triiodobenzoylethyl ester in the polystyrene microspheres. The influence of the weight ratio [2,3,5-triiodobenzoyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…For example, in the presence of 2% PVP with molecular weights of 40 000 and 360 000 g/mol, the size and size distribution of the PMMA microspheres was decreased from 3.0 AE 0.6 to 2.2 AE 0.2 mm, respectively. A similar effect of the stabilizer molecular weight on the average size and size distribution of PS, pentabromobenzyl acrylate and MAOETIB microspheres prepared by dispersion polymerization in the presence of different molecular weights of the stabilizer PVP was reported previously (Bamnolker and Margel, 1996;Galperin et al, 2006;Goldshtein and Margel, 2009b). The explanation for this behaviour is that PVP of a higher molecular weight was adsorbed more strongly to the nucleus surfaces and therefore stabilized the particles more effectively.…”
Section: Effect Of Co-solvent Concentrationsupporting
confidence: 59%
See 1 more Smart Citation
“…For example, in the presence of 2% PVP with molecular weights of 40 000 and 360 000 g/mol, the size and size distribution of the PMMA microspheres was decreased from 3.0 AE 0.6 to 2.2 AE 0.2 mm, respectively. A similar effect of the stabilizer molecular weight on the average size and size distribution of PS, pentabromobenzyl acrylate and MAOETIB microspheres prepared by dispersion polymerization in the presence of different molecular weights of the stabilizer PVP was reported previously (Bamnolker and Margel, 1996;Galperin et al, 2006;Goldshtein and Margel, 2009b). The explanation for this behaviour is that PVP of a higher molecular weight was adsorbed more strongly to the nucleus surfaces and therefore stabilized the particles more effectively.…”
Section: Effect Of Co-solvent Concentrationsupporting
confidence: 59%
“…radiopaque iodinated compounds, magnetic precursors such as iron pentacarbonyl, UV absorbers and others (Shpaisman and Margel, 2005;Galperin et al, 2006;Goldshtein and Margel, 2011). Here, the objective was to use PS and PMMA microspheres for continuous removal of 2-PE formed during the fermentation of S. cerevisiae strain Ye9-612 on L-phe as the nitrogen source.…”
Section: Characterization Of the Ps And Pmma Microspheresmentioning
confidence: 99%
“…These microspheres are widely used in biomacromolecules purification, cell separation [1], enzyme immobilzation [2], biosensors [3,4] and controlled drug delivery [5]. For example, dextran-coated magnetite was used as a drug carrier which allowed a targetable delivery with particle localization in a specific area [6], silane coated ferrite particles was utilized as radioimmunoassay [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploiting good carriers and immobilization strategies has become an interesting work for enzyme immobilization. Recently, preparation of micron-size spheres has attracted wide interest because these microspheres could be utilized in enzyme immobilization [15], biomacromolecules purification [16], cell separation [17], biosensors [18], and controlled drug delivery [19]. Our recent study has demonstrated that the hydrophobic properties of microsphere surface could considerably affect the interaction between carriers and protein [20,21], which suggested that the hydrophobicity should be considered for rational design of enzyme carriers.…”
Section: Introductionmentioning
confidence: 98%